LAND UTILIZATION AND DEVELOPMENT OF VANAME SHRIMP CULTIVATION IN COASTAL AREA, KUBU SUB-DISTRICT, KARANGASEM REGENCY, BALI - Ramadhan, Ahmad Faizal; Wijaya, Nirmalasari Idha; Fatimah, Fatia (Politeknik Kelautan dan Perikanan Dumai, 2024)
The pond land suitability is the most important things in shrimp farming to maintain production and ensure the development of aquaculture businesses. This research aims to determine the outland suitability of the coastal area of Karangasem Regency, evaluate the distribution pattern of cultivation activities and identify regional development factors. This research was a descriptive qualitative study where the analysis results related to mapping of land uses studies are presented descriptively. The data used in this study consisted of primary data: (i) physical-geographic of coastal areas; (ii) public aspirations in coastal areas, and secondary data traced from BPS, Ministry of ATR/BPN Office of Karangasem and PUPR Service Karangasem Regency. The results of this research showed that the spatial analysis of the land suitability in Kubu sub-district showed the land potential with high suitability is 1,009.46 ha; moderate suitability land level is 1,894.01 ha; for coastal areas that do not have potential or are not feasible for developing shrimp water ponds is 799.67 ha. The Kubu sub-district is a center of the shrimp water ponds development in Karangasem Regency, Bali. The existing condition of shrimp water ponds in Kubu sub-district are spread over 3 villages: Sukadana with 20.36 ha; Tianyar in 1,32 ha and West Tianyar with 0.47 ha in area. Through the analysis of internal and external factors of shrimp pond development activities in Kubu Subdistrict, showed that the coastal area of Kubu Subdistrict is very feasible to develop Vannamei shrimp.